Neonatal Gastric Perforation: 14-Year Experience from a Tertiary Neonatal Intensive Care Unit - Sakaria, Rishika P.; Zaveri, Parul G. (American Journal of Perinatology, 2021)
Objective Neonatal gastric perforations (NGPs) are rare and account for 7 to 12% of all gastrointestinal perforations in the neonatal period. The etiology and prognostic factors associated with NGP remain unclear. The aim of this study is to review the cases of NGP in our neonatal intensive care unit (NICU) in the past 14 years and describe the risk factors, clinical presentation, and outcomes associated with it.Study Design A retrospective chart review of neonates with gastric perforation admitted to the NICU between June 2006 and December 2020 was performed. Data regarding their antenatal and neonatal characteristics, laboratory and radiological results, intra-operative findings, hospital course, and outcomes were recorded.Results We identified 350 patients with gastrointestinal perforation at our center during the study period of which 14 (4%; nine males and five females) patients were diagnosed with NGP during surgery. A total of 71% neonates were born preterm (range: 24–39 weeks, median: 34 weeks). Two neonates (14%) were SGA. Only one neonate received cardiopulmonary resuscitation at birth. In all neonates, except two, perforation occurred within the first 10 days of life (median: 4 days, range: 1–22 days). In total, 79% infants received feeds prior to perforation. Ten neonates had a feeding tube, and one neonate had a gastrostomy tube placed prior to perforation. Abdominal distension and pneumoperitoneum were present in all neonates. Majority of the babies had metabolic acidosis (64%) and elevated C-reactive protein (79%). Most (86%) neonates received surgical intervention within 12 hours. Overall survival in our study was 93%.Conclusion NGP is a rare entity seen mostly in preterm infants within the first 10 days of life. Clinical presentation is similar to perforation anywhere along the gastrointestinal tract and definite diagnosis requires exploratory laparotomy. With prompt recognition and surgical intervention, the overall mortality related to neonatal gastric perforation is low.Key Points
Keywords: neonate; pneumoperitoneum; lactobezoar; gastric perforation